2014
DOI: 10.1118/1.4861817
|View full text |Cite
|
Sign up to set email alerts
|

On the determination of reference levels for quality assurance of flattening filter free photon beams in radiation therapy

Abstract: The parameters proposed for the characterization and routine control of stability of profiles of FFF beams appear to be a viable solution with a strong similarity to the conventional parameters used for flattened beams. The results from three different TrueBeams and the cross-validation against a Clinac-iX suggested the possible generalization of the methods and the possibility to use common tolerances for the parameters. The data showed also the reproducibility of beam characteristics among different systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…In similar measurement, Arnfield et al (48) reported a value of 1.34 ± 0.03% for the same MLC model. Profile symmetry was better than 103% for the commissioned field size ranges and the flatness values of 1.03-1.22 were comparable with values reported for a 6 MV FFF beam in literature (50). Penumbra values could be measured with films, offering high spatial resolution, only for a subset of fields required by IEC standard.…”
Section: Discussionsupporting
confidence: 80%
“…In similar measurement, Arnfield et al (48) reported a value of 1.34 ± 0.03% for the same MLC model. Profile symmetry was better than 103% for the commissioned field size ranges and the flatness values of 1.03-1.22 were comparable with values reported for a 6 MV FFF beam in literature (50). Penumbra values could be measured with films, offering high spatial resolution, only for a subset of fields required by IEC standard.…”
Section: Discussionsupporting
confidence: 80%
“…based on the measurement at three different Varian LINACs and used the definition proposed by Fogliata et al . [ 9 , 16 ] while reference values proposed in the current study are based on the measurement at 13 Varian LINACs and used the definition suggested by Sahani et al . [ 10 ] Therefore, reference values determined in this work and reference values reported earlier cannot be compared owing to the difference in definitions except for the field size.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these procedures, the use of the unflatness, slope and peak position has been proposed by Fogliata et al. [ 37 , 38 ]. In our survey, one institution responded that they used such procedures for FFF beam QA.…”
Section: Discussionmentioning
confidence: 99%